Copulatory pattern of the subterranean rodent Ctenomys talarum - Fanjul, Maria Sol (2008)
We describe qualitatively and quantitatively the copulatory pattern of Ctenomys talarum (tuco-tuco) and evaluate it according to that expected for induced ovulators. Mating trials were performed in an experimental apparatus consisting of three chambers. Copulatory pattern of C. talarum is characterized by no lock, pelvic thrusts after intromission and multiple ejaculations. Males may not require multiple intromissions to ejaculate. Courtship starts with agonistic approaches, followed by recognition behaviors, gentle bites, snout pushes and neck exposure. Male mount attempts are frequent (mean 1.2±0.85 attempts/min), while females try to interrupt the mount, suggesting that evasive behavior is an important feature of female C. talarum courtship. The number of copulatory series is variable among couples, but 2-3 are the more frequent cases. Once intromission is achieved, the male starts rapid pelvic thrusts (12 movements/s) of moderate intromission. Later, the male proceeds with deep pelvic thrusts, characterized by deeper intromission and longer duration, (1 or 2 movements/s). The duration of copulatory series is influenced by both the evasive movements of the female and the male interest in continuing mating. Results of this study suggest that the amount of vaginal stimuli provided during mating is crucial for the occurrence of ovulation in C. talarum.